2011
DOI: 10.1142/s0217984911026176
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Magnetoresistance in Perovskite Manganites

Abstract: We have summarized some important results of the anisotropic transport properties of the prototypical manganite La 1−x CaxMnO 3 as well as a few others. The temperature dependence of anisotropic magnetoresistance in manganites exhibits a peak near the magnetic ordering temperature which differs dramatically from the ones in 3d ferromagnetic metals and alloys. Depending on the strain-driven orbital state, the AMR in manganites could be enhanced dramatically. The AMR in manganites is much larger than in ferromag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…At the first glance, this is consistent with the modern consideration [25,31] which predicts that the AMR effect in manganites depends on the field direction relative to the [100] crystallographic axis. This approach, however, is restricted by low temperatures (T<<T C ) and does not take into account the in-plane magnetic anisotropy; thus, it is hardly applicable to our data.…”
Section: Discussionsupporting
confidence: 88%
“…At the first glance, this is consistent with the modern consideration [25,31] which predicts that the AMR effect in manganites depends on the field direction relative to the [100] crystallographic axis. This approach, however, is restricted by low temperatures (T<<T C ) and does not take into account the in-plane magnetic anisotropy; thus, it is hardly applicable to our data.…”
Section: Discussionsupporting
confidence: 88%
“…In short, we will mention the most important results obtained on La 1-x Ca x MnO 3 manganites related to bulk material and films. In the bulk material for x < 0.5 (where the comparison with films was investigated) and at the metal-insulator transition (MIT) a resistivity increase is expected because the charge carriers are scattered by grain boundaries [15]. On the other hand, the MIT temperatures in bulk materials are lower than in thin film samples (of the same composition) suggesting that the epitaxial strain in the films modifies the in-plane and out-of-plane hopping amplitudes that consequently enhance the ferromagnetic transition temperature [16].…”
Section: Introductionmentioning
confidence: 99%
“…were found to decrease with a decreasing film thickness while a reduction in the film thickness increases the magnetoresistance of these films as well as the anisotropy of magnetoresistance [15]. At this point, it is also important to mention that the optical properties study was performed comparing bulk material and films in overdoped region for x > 0.5, with the additional motivation to clarify the role of disorder in the physics of overdoped La 1−x Ca x MnO 3 manganites [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the othorhombic La 0.7 Ca 0.3 MnO 3 (LCMO) with an in-plane lattice constant 3.863 Å can be grown on SrTiO 3 (001) substrate (STO), which has the cubic structure with a lattice constant 3.905 Å such that the lattice mismatch between the STO and the LCMO is only ~1%. AMR has been found to be remarkably large in highly strained ultrathin films as compared to the AMR in thicker films 1,5,6,[9][10][11][12] at certain temperatures below their ferromagnetic Curie temperature (T C ) which is attributed to the increase in the strain as the thickness of the film decreases 12, 13 . In this paper, anisotropy in epitaxial LCMO ultrathin films (4 nm, 6 nm and 8 nm) grown on STO (001) substrate is investigated.…”
mentioning
confidence: 99%
“…al., 9,11 . They could not observe a sign change in the AMR for the LCMO/STO films (down to 7 nm) even though they could observe a change in the sign of the AMR at temperatures below T C in the LCMO/LAO thin films.…”
mentioning
confidence: 99%